High-strength, high-toughness and low-cost recycled PBT / PET alloy material and preparation method thereof
Through the combination of specific components and process steps, a high-strength, high-toughness, and low-cost PBT/PET alloy material is prepared, which solves the degradation problems of PBT materials during injection molding and the stratification problems of PET blends, achieves improved material performance and reduced costs, and is suitable for bathroom products such as toilet seats.
Patent Information
- Application Number
- CN202511161388.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-05
- Filing Date
- 2025-08-19
- Publication Date
- 2025-10-21
AI Technical Summary
In the existing technology, PBT materials are easily degraded during the injection molding process, resulting in a decrease in tensile strength and impact strength. At the same time, the cost of recycling PBT materials is high, and they are easily delaminated when blended with PET, making it difficult to prepare high-performance PBT/PET alloy materials.
Using PBT injection molding secondary materials, recycled PET bottle crushed materials, calcium borate, PTA terephthalate, antimony trioxide, coupling agent, ethylene glycol, toughening agent, carbon nanotubes, chain extender, antioxidant and lubricant as components, through specific process steps and equipment processing, a high-strength, high-toughness and low-cost PBT/PET alloy material is prepared.
It improves the tensile strength and toughness of the material, reduces costs, and expands the application areas of recycled materials, especially showing good performance in bathroom products such as toilet seats.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a high-strength, high-toughness, low-cost recycled PBT / PET alloy material and a preparation method thereof. Background Art
[0002] Polybutylene terephthalate (PBT), a polyester made by the polycondensation of terephthalic acid and butanediol, is a key thermoplastic polyester and one of the five engineering plastics. Its relatively regular chain segments make it a crystalline material with excellent mechanical properties and chemical resistance. Furthermore, its high crystallinity contributes to its high gloss, making it widely used in toilet seat covers in the bathroom industry. It can withstand the erosion of chemicals such as toilet cleaners and maintain its excellent appearance over time.
[0003] However, due to its sensitivity to moisture and temperature, PBT can significantly degrade during the injection molding process, leading to a significant decrease in both tensile and impact strength. PBT is an engineering plastic and is therefore relatively expensive, so the presence of large amounts of secondary material negatively impacts product costs. A modification and recycling solution is urgently needed that can improve the performance of secondary PBT material while increasing costs.
[0004] Polyethylene terephthalate (PET) and PBT share similar groups, suggesting good compatibility. However, due to the denser groups in PET and its higher viscosity, blending with PBT can easily lead to delamination. Consequently, there are limited options for creating PBT / PET alloys for injection molding.
[0005] Chinese invention patent CN104109230B, titled "Continuous Production Method for PBT-PET Copolyester," discloses a method for preparing PBT / PET copolyester via low-molecular-weight polymerization. The process involves beating the ingredients, then subjecting them to separate esterification reactions to produce the esterified PBT and PET, followed by subsequent polymerization in a reactor to produce the resulting material. This approach is only suitable for large-scale petrochemical synthesis plants; conventional modification plants, lacking large reactors and other equipment, are unable to implement the process. However, the present invention utilizes recycled materials through a series of operations to produce a PBT / PET alloy material with superior performance, demonstrating significant economic value. Summary of the Invention
[0006] The problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a high-strength, high-toughness, low-cost recycled PBT / PET alloy material and a preparation method thereof.
[0007] In order to achieve the above object, the solution of the present invention is: A high-strength, high-toughness, low-cost recycled PBT / PET alloy material is prepared from the following components in parts by weight: PBT injection molding secondary material: 100 parts; Recycled PET bottle crushed materials: 30~60 parts; Calcium borate: 2-5 parts; Terephthalic acid PTA: 5-10 parts; Antimony trioxide: 0.1~0.2 parts; Coupling agent: 0.5~1 part; Ethylene glycol: 10-20 parts; Toughening agent: 7~10 parts; Carbon nanotubes: 2-5 parts; Chain extender: 3~5 parts; Antioxidant: 0.5 parts; Lubricant: 1 part.
[0008] Furthermore, the PBT secondary injection molding material is a recycled material of conventional injection molding products, and the recycled PET bottle crushed material is a recycled material obtained by crushing clean recycled transparent PET bottles.
[0009] Furthermore, the calcium borate, PTA terephthalic acid, antimony trioxide, coupling agent, and 5 to 10 parts of ethylene glycol are stirred and mixed in a strict process sequence to prepare a compatibilizer.
[0010] Furthermore, the remaining 5 to 10 parts of ethylene glycol are used as PET depolymerization liquid.
[0011] Furthermore, the toughening agent is ethylene-acrylate-glycidyl methacrylate.
[0012] Furthermore, the carbon nanotubes and the toughening agent are mixed to form a composite toughening agent.
[0013] Furthermore, the chain extender is triglycidyl isocyanurate TGIC.
[0014] Furthermore, the lubricant is compounded with diethylene stearamide TAF and calcium stearate.
[0015] Furthermore, the antioxidant is a mixture of antioxidant 168 and 1010 at a ratio of 1:1.
[0016] A method for preparing a high-strength, high-toughness, low-cost recycled PBT / PET alloy material comprises the following steps: Step 1: adding the calcium borate to ethylene glycol and stirring at 150° C. for 2 to 3 hours to obtain a calcium borate / ethylene glycol colloid; Step 2: Mix the calcium borate / ethylene glycol colloid described in step 1 with the PTA, antimony trioxide, and coupling agent, and continue stirring at 150° C. for 0.5 h to obtain a calcium borate / PET prepolymer material, referred to as mixture 1. Step 3: Mix the recycled PET bottle crushed material with the remaining 5-10 parts of ethylene glycol and stir for 0.5 hours to obtain a mixture 2; Step 4: Weigh the mixture 1 in step 2, the mixture 2 in step 3, and the other components in proportion, put them into a high-speed vacuum kneading mixer, and stir them evenly under vacuum at high speed for 0.5 h to obtain a mixture 3; Step 5: Add the mixture 3 obtained in step 4 into a granulator, heat and extrude it, and then cool and pelletize it to obtain a PBT / PET alloy material.
[0017] Furthermore, the vacuum degree of the high-speed vacuum kneading mixer in step 4 is 1~10kPa, the stirring speed is 800~1000rpm, and the granulator in step 5 is a co-rotating parallel twin-screw extruder granulator, the extrusion temperature of the granulator is 210~230℃, and the screw speed is 200~400rpm.
[0018] Beneficial effects: The present invention prepares a PBT / PET alloy material with the advantages of high strength, high toughness and low cost through reasonable design of the components of the recycled PBT / PET material and improved process operation steps, thereby expanding the application field of the recycled material and having promotion value, especially in the application on toilet seats of bathroom products, with good effects. DETAILED DESCRIPTION
[0019] The present invention discloses a high-strength, high-toughness, low-cost recycled PBT / PET alloy material, which is prepared from the following components in parts by weight: PBT injection molding secondary material: 100 parts; Recycled PET bottle crushed materials: 30~60 parts; Calcium borate: 2-5 parts; Terephthalic acid PTA: 5-10 parts; Antimony trioxide: 0.1~0.2 parts; Coupling agent: 0.5~1 part; Ethylene glycol: 10-20 parts; Toughening agent: 7~10 parts; Carbon nanotubes: 2-5 parts; Chain extender: 3~5 parts; Antioxidant: 0.5 parts; Lubricant: 1 part.
[0020] The PBT secondary injection molding material used in this invention is obtained by crushing and shearing defective products or related gate materials produced after injection molding plastic toilet seat covers using PBT resin with a melt index of 15-25g / 10min (250°C / 2.16kg). Due to the injection molding process, the performance of PBT is significantly degraded, with the tensile strength decreasing from 50-55MPa to approximately 40-45MPa, making it unsuitable for toilet seat production.
[0021] The recycled PET bottle shreds used in this invention are pure, systematically recycled, sorted, and cleaned PET bottle shreds from professional recycling manufacturers. These recycled PET bottle shreds are over 70% less expensive than virgin PBT. Depending on the amount added (30-60 parts), the overall alloy cost can be reduced by approximately 15-25%.
[0022] The compatibilizer, namely the calcium borate / PET prepolymer material, is prepared by mixing calcium borate, poly(terephthalic acid) terephthalate (PTA), antimony trioxide, a coupling agent, and 5 to 10 parts of ethylene glycol in a certain order. The preparation process must be strictly in accordance with the following steps: First, calcium borate is added to ethylene glycol and stirred at 150° C. for 2 to 3 hours to obtain a calcium borate / ethylene glycol colloid; then, the calcium borate / ethylene glycol colloid is mixed with the PTA terephthalate, antimony trioxide, and coupling agent and stirred at 150° C. for 0.5 hours to obtain the calcium borate / PET prepolymer material. Under the catalytic action of antimony trioxide, PTA partially prepolymerizes at 150°C. Calcium borate, treated with a coupling agent, forms strong molecular bonds with PBT and other materials, gradually growing during the mixing process. This process exhibits a dual in-situ polymerization reaction, with simultaneous polyester (polyethylene terephthalate, PET) prepolymerization and calcium borate particle growth. This allows for the uniform dispersion of ultra-low-filled calcium borate in the PET prepolymer without requiring additional steps, with excellent interfacial compatibility. The uniform dispersion of calcium borate nanoparticles significantly improves the crystallinity and mechanical properties of the PBT / PET material. Calcium borate also effectively improves the compatibility between PBT and PET, significantly enhancing the performance of the alloy.
[0023] The ethylene glycol used in the present invention is partially used to prepare the calcium borate / PET prepolymer material, with the remaining portion used as a depolymerization liquid for PET. Recycled PET bottle crushed material is mixed with ethylene glycol and stirred for 0.5 hours, resulting in a viscous mixture that is the result of partial depolymerization of the PET material. Due to its relatively dense terephthalic acid groups, PET material has a high viscosity, making injection molding relatively difficult and has long been used in blow molding or extrusion production processes. Although PBT and PET have similar chemical structures and should be compatible, their significant viscosity difference leads to poor compatibility, resulting in delamination of the mixed material and poor mechanical properties. The present invention uses ethylene glycol to partially depolymerize the PET material, reducing the viscosity of the recycled PET material and enabling it to be more evenly dispersed with the PBT during the blending process. Furthermore, the chain extender added later increases the viscosity of the PBT and simultaneously connects the partially depolymerized PET material to the PBT material, further enhancing their compatibility and significantly improving the material's performance.
[0024] The chain extender used in this invention is triglycidyl isocyanurate (TGIC). Experimental and analytical results indicate that an appropriate amount of TGIC can induce the formation of long-chain branching in PBT / PET, increase the degree of molecular crosslinking, lower the crystallization and melting temperatures of the material, and enhance the tensile strength of the PBT / PET alloy.
[0025] The toughening agent used in this invention is a mixture of ethylene-acrylate-glycidyl methacrylate and carbon nanotubes. The introduction of the carbon nanotubes increases the alloy's elongation at break by nearly 2 times. This is primarily due to the combined action of external force and the carbon nanotubes, which rapidly orient the PBT / PET segments along the stretching direction, resulting in forced, highly elastic deformation and significantly expanding the material's deformability range.
[0026] The lubricant used in the present invention is a mixture of diethylene stearamide (TAF) and calcium stearate. Appropriate amounts of diethylene stearamide (TAF) and calcium stearate can reduce friction between resin particles and between the resin melt and processing equipment, lowering the viscosity of the blend during processing, thereby providing a lubricating effect.
[0027] The present invention also discloses a method for preparing a high-strength, high-toughness, low-cost recycled PBT / PET alloy material, comprising the following steps: Step 1: adding the calcium borate to ethylene glycol and stirring at 150° C. for 2 to 3 hours to obtain a calcium borate / ethylene glycol colloid; Step 2: Mix the calcium borate / ethylene glycol colloid described in step 1 with the PTA, antimony trioxide, and coupling agent, and continue stirring at 150° C. for 0.5 h to obtain a calcium borate / PET prepolymer material, referred to as mixture 1. Step 3: Mix the recycled PET bottle crushed material with the remaining 5-10 parts of ethylene glycol and stir for 0.5 h to obtain a mixture 2; Step 4: Weigh the mixture 1 in step 2, the mixture 2 in step 3, and the other components in proportion, put them into a high-speed vacuum kneading mixer, and stir them evenly under vacuum at high speed for 0.5 h to obtain a mixture 3; Step 5: Add the mixture 3 obtained in step 4 into a granulator, heat and extrude it, and then cool and pelletize it to obtain a high-strength, high-toughness, low-cost recycled PBT / PET alloy material.
[0028] Furthermore, in step 4, the vacuum degree of the high-speed vacuum kneading mixer is 1-10 kPa, and the stirring speed is 800-1000 rpm.
[0029] Furthermore, in step 5, the granulator is a co-rotating parallel twin-screw extruder granulator, the extrusion temperature of the granulator is 210-230° C., and the screw speed is 200-400 rpm.
[0030] The present invention adopts a high-speed vacuum kneading mixer to stir the mixture 1, the mixture 2 and other components at high speed in a vacuum-sealed space, and utilizes the principle that the interaction force of materials in a vacuum is small and more uniformly dispersed, so that the materials are more uniformly dispersed.
[0031] After adopting the above scheme, the present invention prepares recycled PBT / PET alloy materials with the advantages of high strength, high toughness, and low cost through reasonable design of the various components of the PBT / PET alloy materials and improved process operation steps, thereby expanding the application field of the recycled PBT / PET alloy materials and having promotion value, especially for application in toilet seats of bathroom products, with good effects.
[0032] The technical solution of the present invention is further described below with reference to the examples. Where specific techniques or conditions are not specified in the examples, the techniques or conditions described in the literature in the art or in the product instructions were used. Where the manufacturer of the reagents or instruments used is not specified, they are all commercially available conventional products.
[0033] The formula table of this embodiment is shown in Table 1, wherein the PBT injection molding secondary material is self-made in the company; the recycled PET bottle crushed material is commercially available at a cost of about 4 yuan / kg; calcium borate, terephthalic acid PTA, and antimony trioxide are all commercially available; the coupling agent is titanate aluminate, which is commercially available; ethylene glycol is commercially available; the toughening agent is Arkema AX8900 from France; the carbon nanotubes are TG-300 from Shandong Dazhan Nanomaterials Co., Ltd., with a purity of ≥97.5% and a length of 3~10 μm; the chain extender is triglycidyl isocyanurate TGIC from Huangshan TEDA Chemical Co., Ltd., with a purity of 98% and a molecular weight of 297.26; the antioxidant is formed by compounding Jinhai Yabao 168 and 1010 in a ratio of 1:1; the lubricant is formed by compounding Xingtai Guoguang TAF and Hangzhou Sanjin calcium stearate in a ratio of 1:1.
[0034] Table 1 PBT / PET alloy material formula
[0035] Filler preparation steps: 1) Add calcium borate to ethylene glycol and stir at 150°C for 2-3 hours to obtain calcium borate / ethylene glycol colloid; 2) The calcium borate / ethylene glycol colloid was mixed with terephthalic acid (PTA), antimony trioxide, and a coupling agent, and stirred at 150° C. for 0.5 h to obtain a calcium borate / PET prepolymer material, referred to as mixture 1. 3) Mixing the recycled PET bottle crushed material with the remaining ethylene glycol and stirring for 0.5 h to obtain mixture 2; 4) Mixture 1, Mixture 2, and other raw materials were weighed in proportion and placed in a high-speed vacuum kneading mixer. After the vacuum reached 10 kPa, high-speed stirring was started at 800 rpm for 30 minutes to obtain Mixture 3; 5) Adding the mixture 3 to a pelletizer for extrusion, the extrusion equipment is a co-rotating twin-screw parallel extruder pelletizer, the extrusion temperature is 210°C, the screw speed is 300 rpm, and then cooling and pelletizing are performed to obtain a high-strength, high-toughness, low-cost recycled PBT / PET alloy material.
[0036] Table 2 Performance test table of high strength, high toughness and low cost recycled PBT / PET alloy materials
[0037] The performance of the prepared material is tested as shown in Table 2 above. It can be seen from Table 2 that the alloy material has excellent comprehensive performance and can be directly used in the production of toilet covers.
[0038] Among them, sample 0# is a pure PBT secondary material sample, that is, a blank reference sample.
[0039] The specific standards adopted in the above tests are: The tensile strength and elongation at break were determined according to the standard GB / T 1040 “Determination of tensile properties of plastics”, with a test speed of 100 mm / min. Impact strength adopts the standard GB / T 1843 "Determination of Izod Impact Strength of Plastics"; The cost is compared with the price of raw PBT rice based on the cost of input materials.
[0040] As can be seen from the performance table in Table 2 above, the PBT / PET alloy material has excellent comprehensive performance, its mechanical strength is better than that of pure PBT secondary material, and its strength and toughness have reached the level of materials used for ordinary toilet seat covers.
[0041] At the same time, the cost of the alloy material can be as low as 75% of the raw material, which greatly improves the material cost while obtaining materials with the same performance.
[0042] Although the embodiments of the present invention have been shown and described above, it will be understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and purpose of the present invention.
Claims
1. A high-strength, high-toughness, low-cost recycled PBT / PET alloy material, characterized by: Prepared from the following components in parts by weight: PBT injection molding secondary material: 100 parts; Recycled PET bottle crushed materials: 30~60 parts; Calcium borate: 2-5 parts; Terephthalic acid PTA: 5-10 parts; Antimony trioxide: 0.1~0.2 parts; Coupling agent: 0.5~1 part; Ethylene glycol: 10-20 parts; Toughening agent: 7~10 parts; Carbon nanotubes: 2-5 parts; Chain extender: 3~5 parts; Antioxidant: 0.5 parts; Lubricant: 1 part.
2. The high-strength, high-toughness, low-cost recycled PBT / PET alloy material according to claim 1, characterized in that: The PBT secondary injection molding material is a recycled material of conventional injection molding products; the recycled PET bottle crushed material is a recycled material obtained by washing and crushing clean recycled transparent PET bottles.
3. The high-strength, high-toughness, low-cost recycled PBT / PET alloy material according to claim 1, characterized in that: The calcium borate, PTA terephthalic acid, antimony trioxide, a coupling agent and 5 to 10 parts of ethylene glycol are stirred and mixed in a strict process sequence to prepare a compatibilizer.
4. The high-strength, high-toughness, low-cost recycled PBT / PET alloy material according to claim 1, characterized in that: The remaining 5 to 10 parts of ethylene glycol are used as PET depolymerization liquid.
5. The high-strength, high-toughness, low-cost recycled PBT / PET alloy material according to claim 1, characterized in that: The toughening agent is ethylene-acrylate-glycidyl methacrylate.
6. The high-strength, high-toughness, low-cost recycled PBT / PET alloy material according to claim 5, characterized in that: The carbon nanotubes and the toughening agent are mixed to form a composite toughening agent.
7. The high-strength, high-toughness, low-cost recycled PBT / PET alloy material according to claim 1, characterized in that: The chain extender is triglycidyl isocyanurate TGIC.
8. The high-strength, high-toughness, low-cost recycled PBT / PET alloy material according to claim 1, characterized in that: The lubricant is compounded with diethylene stearamide TAF and calcium stearate.
9. A method for preparing a high-strength, high-toughness, low-cost recycled PBT / PET alloy material, comprising the following steps: Step 1: adding the calcium borate described in claim 3 to ethylene glycol, and stirring at 150° C. for 2 to 3 hours to obtain a calcium borate / ethylene glycol colloid; Step 2: Mixing the calcium borate / ethylene glycol colloid described in step 1 with the PTA terephthalate, antimony trioxide, and coupling agent described in claim 3, and stirring at 150° C. for 0.5 h to obtain a calcium borate / PET prepolymer material, referred to as mixture 1. Step 3, mixing the recycled PET bottle crushed material described in claim 2 with the remaining 5 to 10 parts of ethylene glycol described in claim 4 and stirring for 0.5 hours to obtain a mixture 2; Step 4, weighing the mixture 1 described in step 2, the mixture 2 described in step 3, and the other components described in claim 1 in proportion, putting them into a high-speed vacuum kneading mixer, and stirring them uniformly under vacuum high speed for 0.5 h to obtain a mixture 3; Step 5: Add the mixture 3 obtained in step 4 into a granulator, heat and extrude it, and then cool and pelletize it to obtain a PBT / PET alloy material.
10. The method for preparing a high-strength, high-toughness, low-cost recycled PBT / PET alloy material according to claim 9, characterized in that: The vacuum degree of the high-speed vacuum kneading mixer in step 4 is 1~10kPa, and the stirring speed is 800~1000rpm; the granulator in step 5 is a co-rotating parallel twin-screw extruder granulator, the extrusion temperature of the granulator is 210~230℃, and the screw speed is 200~400rpm.
Citation Information
Patent Citations
Continuous production method of PBT-PET copolyester
CN104109230A
